Efektivitas Model Project-Based Learning Terintegrasi STEM dalam Peningkatan Motivasi Siswa pada Pembelajaran PJOK - Prasetiyo, Rahayu; Synthiawati , Novita Nur (MAN Insan Cendekia Jambi, 2025)
This research evaluates the effectiveness of a STEM-integrated Project-Based Learning (PjBL) model in enhancing students’ motivation in Physical Education (PJOK), particularly in the rounders (kasti) unit. Utilizing a quantitative approach with a quasi-experimental design, the study involved 30 fifth-grade students at SDN Mayangan selected through total sampling. The motivation questionnaire measured both intrinsic and extrinsic motivational factors. Results from the normality test confirmed that the data were normally distributed, and the paired sample t-test showed a significant improvement in motivation following the intervention (p = 0.000). Students’ average motivation scores increased from 37.30 to 40.47, demonstrating that the STEM-integrated PjBL model effectively boosts learning motivation.